2013
DOI: 10.1097/brs.0b013e318278ebe8
|View full text |Cite
|
Sign up to set email alerts
|

Is Type of Compensation a Predictor of Outcome After Lumbar Fusion?

Abstract: This study demonstrates a difference in outcomes after lumbar spinal fusion between long-term disability and workers' compensation populations. Although, these populations achieve only marginal improvement, it seems that the type of compensation status influences outcome. Workers' compensation has a clear, negative influence on outcome when compared with controls, whereas well-selected patients receiving disability compensation seem more likely to benefit from lumbar fusion. Therefore, surgeons and researchers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 32 publications
2
42
1
1
Order By: Relevance
“…1,10,12,13,17,20,21,[23][24][25][26]30,32,35,36,39,42,43 Patients may show improvement from preoperative or injury state but tend not to do as well as non-workers' compensation patients.…”
Section: Discussionmentioning
confidence: 92%
“…1,10,12,13,17,20,21,[23][24][25][26]30,32,35,36,39,42,43 Patients may show improvement from preoperative or injury state but tend not to do as well as non-workers' compensation patients.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, it has been previously suggested that the compensation status may significantly affect the long-term surgical outcomes after lumbar fusion [10,29]. As such variable was not analyzed in the present study, there is a possibility that the compensation status of the groups under analysis in the present were not perfectly matched at the baseline, although in every step (both when considering the studied variables isolatedly and in combination) the groups presented no difference regarding age, preoperative ODI total and preoperative VAS/back pain.…”
Section: Discussionmentioning
confidence: 99%
“…These factors create the confounding variable of secondary gain that may hinder the patient’s motivation to improve. Multiple studies have demonstrated that patients receiving workers’ compensation respond poorly to spine surgeries compared with nonworkers’ compensation in nearly all outcome variables including postoperative pain levels, postoperative opioid use, functional ability after surgery including ability to work, and overall emotional well-being 1315…”
Section: Etiologymentioning
confidence: 99%